A pilot study of a telehealth family‐focused melanoma preventive intervention for children with a family history of melanoma. Issue 1 (10th November 2019) - Wu, Yelena P.; Boucher, Kenneth; Hu, Nan; Hay, Jennifer; Kohlmann, Wendy; Aspinwall, Lisa G.; Bowen, Deborah J.; Parsons, Bridget G.; Nagelhout, Elizabeth S.; Grossman, Douglas; Mooney, Kathi; Leachman, Sancy A.; et al.
Abstract: Objective: Melanoma preventive interventions for children with familial risk are critically needed because ultraviolet radiation (UVR) exposure and sunburn occurrence early in life are the primary modifiable risk factors for melanoma. The current study examined the feasibility and acceptability of a new, family‐focused telehealth intervention for children with familial risk for melanoma and their parents. The study also explored changes in child sun protection and risk behaviors, sunburn occurrence, and objectively measured UVR exposure. Methods: This was a prospective study with a single‐group design (n = 21 parent‐child dyads, children ages 8‐17). Dyads were asked to participate in three in‐person assessments and three live video teleconference intervention sessions. Results: The intervention was feasibly delivered, and the intervention content was acceptable to parents and children. The intervention was associated with improvements in child use of certain sun protection strategies over time and declines in child UVR exposure. Conclusions: A telehealth‐delivered, family‐focused melanoma preventive intervention was feasibly delivered and was acceptable to parent‐child dyads. Future melanoma preventive interventions for this at‐risk population could incorporate eHealth technologies to facilitate improvements in use of sun protection and monitoring of UVR exposure. This trial was registered with Clinicaltrials.gov, number NCT02846714.